A unique method to disperse Au nanoparticles at ultra-high loading via LDH intercalation chemistry. Issue 7 (31st January 2019) - Du, Yi; Wooler, Bradley; Weiss, Brian; Kliewer, Chris; Miseo, Sabato; Soled, Stuart
Abstract : A facile synthesis of small well dispersed gold clusters (1.7 nm) is successfully performed at ultra-high loading (62.8 wt%) using a layered double hydroxide (LDH) as a support. Abstract : A facile synthesis of small well dispersed gold clusters (1.7 nm) is successfully achieved at ultra-high loading (62.8 wt%) using a layered double hydroxide (LDH) as a support. The LDH needs to be anion exchanged with terephthalic acid to expand the interlayer distance prior to accommodating Au precursors. The Au nanoparticles in between LDH layers are still accessible, demonstrated by favourable CO oxidation. This finding provides a novel method to disperse a large amount of Au nanoparticles on a support without severe aggregation.